2007
DOI: 10.1590/s0102-33062007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição de quintais agroflorestais na conservação de plantas da Caatinga, Município de Caruaru, PE, Brasil

Abstract: RESUMO -(Contribuição de quintais agroflorestais na conservação de plantas da Caatinga, Município de Caruaru, PE, Brasil). A presente pesquisa foi realizada na zona rural do município de Caruaru, tendo como objetivo estudar a diversidade florística e a contribuição de quintais agroflorestais para a conservação da diversidade local. O trabalho foi conduzido a partir de entrevistas semi-estruturadas, associadas à técnica da turnê-guiada, realizada com os mantenedores dos quintais. Paralelamente, fez-se medição d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
102

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 29 publications
0
35
1
102
Order By: Relevance
“…Das 48 plantas relacionadas por Albuquerque & Andrade (2002b) para área de Caatinga no agreste pernambucano, 34 eram nativas; enquanto no estudo realizado no município de Jupi por Teixeira & Melo (2006), das 106 espécies reportadas apenas 27 eram nativas da região. Já Florentino et al (2007) verificaram que das 84 espécies no município de Caruaru, 28 representavam plantas nativas. O número relativamente alto de espécies nativas com uso medicinal no presente trabalho (62) deve-se ao fato de que, o objeto de estudo enfocou somente as plantas nativas.…”
Section: Resultado E Discussãounclassified
“…Das 48 plantas relacionadas por Albuquerque & Andrade (2002b) para área de Caatinga no agreste pernambucano, 34 eram nativas; enquanto no estudo realizado no município de Jupi por Teixeira & Melo (2006), das 106 espécies reportadas apenas 27 eram nativas da região. Já Florentino et al (2007) verificaram que das 84 espécies no município de Caruaru, 28 representavam plantas nativas. O número relativamente alto de espécies nativas com uso medicinal no presente trabalho (62) deve-se ao fato de que, o objeto de estudo enfocou somente as plantas nativas.…”
Section: Resultado E Discussãounclassified
“…Ferraz et al 2006, Florentino et al 2007, Lucena et al 2007, 2008, Monteiro et al 2006, Ramos et al 2008a, 2008b, Sá et al 2009). Lucena et al (2012b) identified that one of the most important species for the community Pau D'Arco (Itaporanga, Paraíba state) was in the list of endangered species, according to IBAMA and MMA (2008).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…In order to understand the relationship between knowledge and the use of natural resources of the Caatinga by human populations, studies with an ethnobotanical approach have been carried out in this natural environment, from general surveys to hypothesis tests, to identify use pressures on biodiversity and suggest sustainable and conservationist alternatives (Florentino et al 2007, Lucena et al 2012a, Lucena et al 2012b, Lucena et al 2014, Monteiro et al 2008, Ramos et al 2008a, 2008b, Ribeiro et al 2014a, 2014b, Sá et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…428 (2006). There are no detailed maps of the the Caatinga so classifying this phytophysiognomy was based on municipality, as done by Araújo et al (2007). If a study was conducted in Carrasco, a xerophytic vegetation in the Northeast Region of Brazil (Andrade-Lima 1978), it was recorded as occurring in the Caatinga.…”
Section: Classification Of the Phytophysiognomies And Mapping The Revmentioning
confidence: 99%
“…Within the original territories of these two ecosystems, there have been several ethnobotanical studies about local communities and native plant resources from different vegetation formations, such as dense ombrophilous forest (Pinto et al 2006), restinga (Melo et al 2008), mixed ombrophilous forest (Althaus-Ottmann et al 2011) and seasonal semideciduous forest (Eichemberg et al 2009), as well as distinct vegetation formations found in the Caatinga (Albuquerque & Andrade 2002a; Florentino et al 2007;Roque et al 2010).…”
Section: Introductionmentioning
confidence: 99%